Omalus puncticollis - Paukkunen, Juho; Rosa, Paolo; Soon, Villu; Johansson, Niklas; Ødegaard, Frode (Zenodo, 2014)
6. Omalus puncticollis (Mocsáry, 1887) Ellampus puncticollis Mocsáry 1887: 291. Lectotype ♀ (designated by Móczár 1964a: 435), Germany: Hanover (MNSB) (examined). Omalus aeneus [nec (Fabricius, 1787)]: Johansson 2010: 118 [part.], Johansson 2011: 35. Omalus puncticollis : Hallin 2012, Dyntaxa 2013. Material examined. * Norway (total 12 exx.): TEI : Seljord, Heggenes; TEY : Kragerø, Jomfruland; Porsgrunn, Hellås; Porsgrunn, Prestemoen; Bamble, Langøya; VAY : Kristiansand, Nedre Timenes; VE : Larvik, Mølen; Horten, Løvøya; Tjøme, Kolabekk-kilen. Sweden (total 3 exx.): Sm : Vetlanda, Skirö; Karlstorp, Drags Udde; Upl : Ljusterö, Hummelmora. Distribution. * Norway, Sweden —Westpalearctic (?): Europe, Asia Minor and North Africa (Linsenmaier 1959, 1968, 1999). The general distribution is poorly known, because many authors have considered O. puncticollis to be conspecific with O. aeneus . Remarks. The status of this taxon has varied considerably in the literature. While some authors have considered it to be a valid species (e.g. Morgan 1984, Kunz 1994, Rosa 2006) others have classified it as a form of O. aeneus (e.g. Trautmann 1927, Linsenmaier 1959, 1997, Kimsey & Bohart 1991, Mingo 1994). Recent unpublished DNA COI barcode studies suggest that O. puncticollis significantly differs genetically from O. aeneus , and most likely should be classified as a distinct species. Morphological and ecological differences have not yet been studied in detail, but apparently O. puncticollis is characterized by large mesonotal punctures, relatively hairy mesonotum, and a deep posteromedian notch on the third tergite. So far, the occurrence of O. puncticollis has been confirmed from Norway and Sweden by DNA barcoding. The distribution of the species is still poorly known in the studied area. : Published as part of Paukkunen, Juho, Rosa, Paolo, Soon, Villu, Johansson, Niklas & Ødegaard, Frode, 2014, Faunistic review of the cuckoo wasps of Fennoscandia, Denmark and the Baltic countries (Hymenoptera: Chrysididae), pp. 1-67 in Zootaxa 3864 (1) on pages 10-11, DOI: 10.11646/zootaxa.3864.1.1, http://zenodo.org/record/4930433 : {"references": ["Mocsary, A. (1887) Eine neue Goldwespen-Art und - Varietat aus Deutschland. Entomologische Nachrichten, 13, 291.", "Moczar, L. (1964 a) Ergebnisse der Revision der Goldwespenfauna des Karpatenbeckens. Acta Zoologica, 10, 433 - 450.", "Fabricius, J. C. (1787) Mantissa Insectorum sistens eorum species nuper detectas adiectis characteribus genericis, differentiis, specificis, emendationibus, observationibus. Tom. I. Impensis Christ. Gottl. Froft., Hafniae, xx + 348 pp. http: // dx. doi. org / 10.5962 / bhl. title. 11657", "Johansson, N. (2010) Solitara gaddsteklar (Hymenoptera: Aculeata) pa tre torrangsartade lokaler i Ovre Emadalen. Entomologisk Tidskrift, 131, 113 - 130.", "Johansson, N. (2011) Brandinsekter pa Drags udde. Uppfoljning av naturvardsbranningen 2006. Lansstyrelsen i Jonkopings lan, Meddelande 2011: 03, 36 pp.", "Hallin, G. (2012) Gaddsteklar i Orebro lan - 60 ars eget samlande och en sammanstallning av befintlig kunskap. Lansstyrelsen i Orebro lan, Publ. Nr 2012: 39, 73 pp.", "Dyntaxa (2013) Svensk Taxonomisk Databas - Swedish Taxonomic Database (version 1.1.5059.20729). Available from: http: / / www. dyntaxa. se / (accessed 1 November 2013)", "Linsenmaier, W. (1959) Revision der Familie Chrysididae (Hymenoptera) mit besonderer Brucksichtigung der europaischen Spezies. Mitteilungen der Schweizerischen Entomologischen Gesellschaft, 32, 1 - 232.", "Linsenmaier, W. (1968) Revision der Familie Chrysididae (Hymenoptera), Zweiter Nachtrag. Mitteilungen der Schweizerischen Entomologischen Gesellschaft, 41, 1 - 144.", "Linsenmaier, W. (1999) Die Goldwespen Nordafrikas (Hymenoptera, Chrysididae). Entomofauna, 10 (Supplement), 1 - 281.", "Morgan, D. (1984) Cuckoo-wasps, Hymenoptera, Chrysididae. Handbooks for the Identification of British Insects, Vol. 6, Part 5, Royal Entomological Society of London, London, 37 pp.", "Kunz, P. X. (1994) Die Goldwespen (Chrysididae) Baden-Wurttembergs. Taxonomie, Bestimmung, Verbreitung, Kartierung und Okologie. - Mit einem Bestimmungsschlussel fur die deutschen Arten. Beihefte zu den Veroffentlichungen fur Naturschutz und Landschaftspflege in Baden-Wurttemberg, 77, 1 - 188.", "Rosa, P. (2006) I Crisidi della Valle d'Aosta (Hymenoptera, Chrysididae). Monografie del Museo Regionale di Scienze Naturali, 6, St. - Pierre, Aosta, 368 pp., xvi + 32 pls.", "Trautmann, W. (1927) Die Goldwespen Europas. Uschman, Weimar, 194 pp. + 2 pls.", "Linsenmaier, W. (1997) Die Goldwespen der Schweiz. Veroffentlichungen aus dem Natur-Museum Luzern, 9, 1 - 139.", "Kimsey, L. S. & Bohart, R. M. (1991 [\" 1990 \"]) The Chrysidid Wasps of the World. Oxford Press, New York, 652 pp."]}